Verdir le diplôme d’architecture au Canada : un forum académique national, une question de transdisciplinarité. - Céline-Coralie Mertenat; Daniel Pearl; Carmela Cucuzzella (VertigO)
In order to address the challenges of sustainable development in academia, Université de Montreal, has been participating in a project called “Greening the (Architecture) Curriculum in Canada”. This is an ongoing, collective project for sharing ideas, resources and experiences on integrating sustainable development within the core curriculum of architectural schools across Canada. In this virtual forum, each university has the opportunity to present questions on major issues, to debate, and finally, to respond. It provides a rich, reflective and deliberative forum for exchanging on common, and at times, diverging ideas related to current and potential structures for architectural curricula, including what tools and models may be most appropriate. The objective of this article is to present this unique experience which has spanned over the last decade.